"DROPPING THE BALL": The Understudied Nexus of Sports and Politics. (March 2017) - Gift, Thomas; Miner, Andrew
From the Roman Colosseum to the Yankee Stadium, the Olympics to the Super Bowl, sports have always played a central role in societies. With so much at stake—money, pride, power (and occasionally even fun)—sports are undeniably political. Yet despite this recognition, political scientists and policy scholars devote little attention to the study of sports, especially compared with other disciplines like business, law, and economics. We offer reasons for this void and suggest how political scientists can begin to fill it. In our view, the nexus between sports and politics is not only a vital topic of study on its own, but it can also provide a lens through which to examine—and test—broader questions in the discipline. We propose how scholars can think more systematically about the interaction of politics and sports and leverage the distinctive qualities of sports to improve causal identification across a range of issue areas and subfields in political science and policy studies.